GROWTH MINDSET DAN KETEKUNAN BELAJAR SISWA SMP DALAM KONTEKS PEMBELAJARAN DI JAKARTA - R. Akbar, DA. Purwandari, Saipiatuddin (FKIP UMN ALWASHLIYAH, 2026)
This study aims to describe the profile of growth mindset and learning persistence of ninth-grade students in Social Studies (IPS) at SMP Negeri 163 Jakarta. The low level of learning persistence and suboptimal growth mindset among students served as the empirical basis for this study. Data were collected from 139 ninth-grade students using a Likert-scale questionnaire developed based on Dweck's (2006) theory and Costa & Kallick's (2014) framework. This study employs a descriptive qualitative approach by utilizing empirical data from a previous study as the primary information source. The findings reveal that the majority of students fall into the moderate category for both constructs (growth mindset: 68.3%; learning persistence: 69.8%). Continuum line analysis shows that the dimension of response to failure is the greatest strength in students' growth mindset (mean 4.31), while accuracy and attention to detail is the highest dimension in learning persistence (mean 4.24). The dimensions of attitude toward challenges and ability to maintain focus still require further development. These findings carry significant implications for Social Studies teachers in designing instruction that actively cultivates students' growth mindset and learning persistence.